HIGH VOLTAGE INSULATION STUDIES. - Lau, Kwan Yiew, 1984-, editor; Ahmad Darus, contributor; Herlina Abdul Rahim, 1973-, contributor; Lim, Yee Sin, contributor; Mohamed Afendi Mohamed Piah, contributor; Mohd. Muhridza Yaacob, contributor; Muhammad Faisal Agos, contributor; Nor Asiah Muhamad, contributor; Rubiatul Addawiyah Zainir, contributor; Yanuar Zulardiansyah Arief, contributor (Johor Bahru, Johor : Penerbit UTM Press, 2015)
Includes bibliographical references and index :p.48